2014
DOI: 10.47102/annals-acadmedsg.v43n8p428
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Ray Amputation in Diabetic Foot Patients

Abstract: Dear Editor,Diabetes mellitus is a growing problem in Singapore, with a reported incidence of 11.3% of the Singapore population, a signifi cant increase from 8.2% in 2004. 1 With the implementation of a multidisciplinary approach combined with a clinical pathway, our major amputation rate (below-and above-knee amputation) has been reduced from 31.15% in 2002 to 11.01% in 2007. 2 Nather et al in 2008 identifi ed predictive factors leading to limb loss in diabetic patients to be peripheral vascular disease and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…2,11,15 This rate is greater than, but comparable to, other studies’ findings. Wong et al 16 reported a 50% 1-year ambulation rate in a patient cohort similar to ours. Norvell et al and Columbo et al both reported 40% of patients maintaining preoperative ambulatory status following BKA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…2,11,15 This rate is greater than, but comparable to, other studies’ findings. Wong et al 16 reported a 50% 1-year ambulation rate in a patient cohort similar to ours. Norvell et al and Columbo et al both reported 40% of patients maintaining preoperative ambulatory status following BKA.…”
Section: Discussionsupporting
confidence: 87%
“…2,11,15 This rate is greater than, but comparable to, other studies' findings. Wong et al 16 20,21 Furthermore, it remains evident that ambulation outcomes have trended downward over the years. In 1987, Francis and Renton 22 reported 85% successful ambulation in a cohort of 46 patients after BKA.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al . also found that indicators of poor vascularization such as low ankle brachial index and absence of popliteal pulse were negative predictors of prosthetic rehabilitation ( 2 ). Further investigation should identify factors which improve outcome after TTA in patients with insufficient flow in the popliteal artery.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, this ratio ranges from 49% ( 14 ) to over 95% ( 15 ). A similar time frame of 12 months was used in previous researches ( 2 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and type II diabetes are leading risk factors for cardiovascular disease, particularly known to increase the prevalence of peripheral arterial disease (PAD) 1–3 . PAD is characterized by impaired blood supply to the limb musculature due to large artery occlusion or regression of local blood vessels in the limbs.…”
Section: Introductionmentioning
confidence: 99%